Electrophysiological evidence that TRPM3 is a candidate in latent spinal sensitization of chronic low back pain - Wang, Dan; Treede, Rolf-Detlef; Koehr, Georg (Neuroscience letters, 2023)
Latent spinal sensitization is one key mechanism developing at the early stage of chronic low back pain (LBP). TRPM3-mediated calcium transients of dorsal root ganglia (DRG) neurons are considered critical presynaptic signals involved in this latent sensitization. However, postsynaptic consequences in input laminae of the spinal cord have not been addressed so far. Here, by electrophysiological recordings in acute spinal cord slices from adult rats, we show that perfusion of the TRPM3 agonist pregnenolone sulfate (PregS) induced a significant increase in the frequency but not amplitude of spontaneous postsynaptic currents in lamina I and II neurons. This frequency increase started slowly during PregS perfusion but was reversible following washout. This result is consistent with a presynaptic action of the neurosteroid PregS, indicating the presynaptic expression of functional TRPM3 in the superficial dorsal horn of adult rats. Thus, PregS-induced TRPM3 activation enhances spinal synaptic strength, implying a mediating role of TRPM3 between neuroendocrine and nociceptive signaling, which might as well exist in chronic LBP primed by chronic stress that promotes the biosynthesis of PregS.
Online veröffentlicht: 5. Oktober 2023, Artikelversion: 10. Oktober 2023
Gesehen am 08.10.2024